Highly Sensitive On-Skin Temperature Sensors Based on Biocompatible Hydrogels with Thermoresponsive Transparency and Resistivity - Park, Tae Hyun; Park, Seongjin; Yu, Seunggun; Park, Sangun; Lee, Junseok; Kim, Sunho; Jung, Youngmee; Yi, Hyunjung (WILEY, 2021)
The development of electrically responsive sensors that interact directly with human skin and at the same time produce a visual indication of the temperature is in great demand. Here, we report a highly sensitive electronic skin (E-skin) sensor that measures and visualizes skin temperature simultaneously using a biocompatible hydrogel displaying thermoresponsive transparency and resistivity resulting from a temperature dependence of the strength of the hydrogen bonding between its components. This thermoresponsive hydrogel (TRH) showed a temperature dependence of not only the proton conductivity but also of its transmittance of light through a change in polymer conformation. We were able to use our TRH temperature sensor (TRH-TS) to measure temperature in a wide range of temperatures based on a change in its intrinsic resistivity (-0.0289 degrees C-1) and to visualize the temperature due to its thermoresponsive transmittance (from 7% to 96%). The TRH-TS exhibited high reliability upon multiple cycles of heating and cooling. The on-skin TRH-TS patch is also shown to successfully produce changes in its impedance and optical transparency as a result of changes in skin temperature during cardiovascular exercise. This work has shown that our biocompatible TRH-TS is potentially suitable as wearable E-skin for various emerging flexible healthcare monitoring applications.
Keywords: NETWORK HYDROGELS; STRAIN